NOKIA PHONE TREATMENT APPLICATIONS USING Macromedia Dreamweaver MX - Taufik Zulfika (Jurnal Sistem Informasi, 2008)
Â  Program the Nokia Care application is built using Macromedia Dreamweaver MX program whose goal is to make the program a web application that displays various information about nokia phone care accessible people, so that more mobile phone users to know. Use Table, Link and others in making this program a facility has been provided by Macromedia Dreamweaver MX to make it easier for it to make a web page.